International nurse recruitment and NHS vacancies: a cross-sectional analysis - Batata Amber S (BMC, 2005)
Abstract Background Foreign-trained nurse recruits exceeded the number of new British-trained recruits on the UK nurse register for the first time in 2001. As the nursing shortage continues, health care service providers rely increasingly on overseas nurses to fill the void. Which areas benefit the most? And where would the NHS be without them? Methods Using cross-sectional data from the 2004 Nursing and Midwifery Council register, nurse resident postcodes are mapped to Strategic Health Authorities to see where foreign recruits locate and how they affect nurse shortages throughout the UK. Results Areas with the highest vacancy rates also have the highest representation of foreign recruits, with 24% of foreign-trained nurses in the UK residing in the London area and another 16% in the SouthEast (comparable numbers for British-trained nurses are 11% and 13%, respectively). Without foreign recruitment, vacancy rates could be up to five times higher (three times higher if only Filipino recruits remained). Conclusion The UK heavily relies on foreign recruitment to fill vacancies, without which the staffing crisis would be far worse, particularly in high vacancy areas.